Evaluating investment in common stocks using net present value and internal rate of return - an applied study - محمد علي ابراهيم العامري,; عبد الله علي احمد القريشي, (Iraqi Journal for Administrative Sciences, 2024)
The topic of valuing common shares and determining the value of the share is one of the topics that has received a great deal of attention in light of the multiple evaluation methods and factors affecting the value of the share inside and outside the facility. Net present value and internal rate of return are also popular methods. It has a great deal of importance in the financial literature. It is the basis for studying these two methods for evaluating capital investments, but modern financial literature has used them to consider investment in common stocks. The net present value is a sound criterion for evaluating investment in ordinary shares. The more the company can maximize the true value of its ordinary shares, thus making the net present value of investment in shares positive, the closer it is to achieving its main goal, which is embodied in maximizing the owners' wealth. The internal rate of return is also a sound criterion for evaluating investment in common stocks, as it is compared with the rate of return required for the cost of financing. Companies that do not achieve a return from their investment that at least covers the cost of their funding must reconsider their investment policy.